Mapping Region-Specific Longitudinal Cortical Surface Expansion from Birth to 2 Years of Age - Gang Li; Jingxin Nie; Li Wang; Feng Shi; Weili Lin; John H. Gilmore; Dinggang Shen (2012)
The human cerebral cortex develops rapidly and dynamically in the first 2 years of life. It has been shown that cortical surface expansion from term infant to adult is highly nonuniform in a cross-sectional study. However, little is known about the longitudinal cortical surface expansion during early postnatal stages. In this article, we generate the first longitudinal surface-based atlases of human cortical structures at 0, 1, and 2 years of age from 73 healthy subjects. On the basis of the surface-based atlases, we study the longitudinal cortical surface expansion in the first 2 years of life and find that cortical surface expansion is age related and region specific. In the first year, cortical surface expands dramatically, with an average expansion of 1.80 times. In particular, regions of superior and medial temporal, superior parietal, medial orbitofrontal, lateral anterior prefrontal, occipital cortices, and postcentral gyrus expand relatively larger than other regions. In the second year, cortical surface still expands substantially, with an average expansion of 1.20 times. In particular, regions of superior and middle frontal, orbitofrontal, inferior temporal, inferior parietal, and superior parietal cortices expand relatively larger than other regions. These region-specific patterns of cortical surface expansion are related to cognitive and functional development at these stages.